A rare disease patient registry - Elias, Jaan, (SAGE Business cases., 2021)
Michael Hund, CEO of Epidermolysis Bullosa Research Partnership (EBRP), had arrived at a fork in the road. He faced a decision on the structure of an entity he had created with help from a cloud computing industry leader for a database of health information about Americans struggling with epidermolysis bullosa (EB). Should he spin out the new entity from EBRP into a for-profit venture? He had offers from venture capitalists and investors to capitalize a for-profit company. Or should he stay with the tried-and-true model for medical charities and establish a non-profit to hold the database? Both options offered opportunities and challenges.